Educational Communication for Raising Awareness of Hygiene and Healthy Life in Tirtayasa, Serang, Banten - Eva Hutri Sinaga; Mutia Nurdalilah Simatupang; Ikrimatul Amal; Ail Muldi; Neka Fitriyah (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2023)
Tirtayasa village is one of the villages in the District Tirtayasa, Serang, Banten province. The Ciujung River traverses this area, which is one irrigation source for agriculture and Fisheries. The main problem of the Tirtayasa Village community is the lack of awareness of healthy and clean living, especially the problem of waste and the use of river water for daily needs. The communication model used in this service is through applying the concepts of behaviorism theory by J.B. Watson, with educational messages delivered persuasively. The method used is quantitative with an experimental method through pre-test and post-test. In these tests, we provided questions to measure public knowledge. The results of the activities in Tirtayasa Village are, firstly, the procurement of waste disposal sites so that people no longer throw garbage in the river. Secondly, the source of clean water for daily needs, especially for consumption, and thirdly coordination and cooperation between the local government and companies or factories that are indicated to drain waste into the river.